Biomarkers of response to therapy in oesophago-gastric cancer. Issue 1 (17th December 2008) - Fareed, K R; Kaye, P; Soomro, I N; Ilyas, M; Martin, S; Parsons, S L; Madhusudan, S
Abstract : Cancer of the oesophagus, gastro-oesophageal junction (GOJ) and stomach remains a major health problem worldwide. The evidence base for the optimal management of patients with operable oesophago-gastric cancer is evolving. Accepted approaches include preoperative chemotherapy followed by surgery (oesophageal cancer), chemo-radiotherapy alone (oesophageal cancer) and perioperative chemotherapy (gastric and gastro-oesophageal adenocarcinomas). The underlying principles behind neoadjuvant therapy are to improve resectability of the tumour by tumour shrinkage/downstaging and to treat occult metastatic disease as early as possible. The response rate to cytotoxic therapy is about 40% in oesophago-gastric cancer. Available evidence suggests that a favourable histopathological response to cytotoxic therapy may be a useful positive predictive marker in oesophago-gastric cancer. However, the ability to predict tumour response in routine clinical practice is difficult and is an area of intense investigation. There is evolving evidence for the role of predictive biomarkers in cancer in general and oesophago-gastric cancer in particular. We provide an overview on the current status of radiological and biological predictive biomarkers. We have focussed on clinical translational investigations and, where appropriate, provided pre-clinical insights. Whether predictive markers will be routinely incorporated in clinical practice remains to be seen as biomarker research is expensive and the data generated from these investigations are complex. It is clear that a concerted international effort between academia and industry is critical if personalised medicine as a practical reality for our cancer patients is to be realised.